APPLICATION OF NEW METHODS AND FORMS OF FINANCIAL SECURITY FOR AIC OF KAZAKHSTAN IN THE CONDITIONS OF ECONOMIC MODERNIZATION - Ramazanova Shynar Shaimuratovna; Kuchukova Nurilya Kenzhebekovna; Shmarlovskaya Galina Alexandrovna; Varaksa Natalia Gennadyevna; Abdulova Oryntai Saltaevna; Abdrakhmanova Nursulu Bakhitovna (Scientific Journal of Pedagogy and Economics, 2021)
Kazakhstan, due to its inherent natural, climatic and geographical features, as well as specific conditions and traditional labor skills of the indigenous population, has long been considered one of the largest livestock countries. In Kazakhstan, almost half of the population lives in the countryside, but it is agriculture that has become the weakest sector, which requires a properly selected consistent approach to reform. In order to create conditions for the development of the innovative potential and innovative activity of the agricultural sector and the formation of a saturated market for products and services, it is necessary to determine the factors of the crisis state of agriculture and justify ways to overcome them, given the existing prerequisites and opportunities. There is always a lag of the actual results of agricultural production from the possibilities of obtaining them with the full and correct use of scientific and technical achievements. This is also true for the present. For example, the productive potential of plants and animals is realized at a level not exceeding 35-40% genetically determined. The possibilities of increasing soil fertility are used at the same level. Along with the development of scientific research, this requires increasing the innovative potential in all other areas, increasing the possibilities for a wider and more efficient use of the existing and expected in the future scientific and technological achievements.